2006
DOI: 10.1111/j.1460-9568.2006.04923.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cerebrovascular effects of MDMA and acute responses to the drug

Abstract: Acutely, 3,4,-methylenedioxymethamphetamine (MDMA) induces cerebrovascular dysfunction [Quate et al., (2004)Psychopharmacol., 173, 287-295]. In the longer term the same single dose results in depletion of 5-hydroxytrptamine (5-HT) nerve terminals. In this study we examined the cerebrovascular consequences of this persistent neurodegeneration, and the acute effects of subsequent MDMA exposure, upon the relationship that normally exists between local cerebral blood flow (LCBF) and local cerebral glucose utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 84 publications
3
20
0
Order By: Relevance
“…A single acute administration of MDMA has previously been shown to increase metabolic activity in most brain areas (Balogh et al,2004; Quate et al,2004; Ando et al,2006), whereas CBF was decreased (Quate et al,2004). The present study is, however, in keeping with previous chronic studies (Ferrington et al,2006) and showed a persistent effect of repeated MDMA treatment upon CMRG, with increases in a few areas against a more general background of decreased activity in the majority of ROIs, but a relative increase in CBF. Given the close relationship that normally exists between the metabolic demands of brain tissue and the CBF, the relative hyperperfusion identified in these animals must reflect lesion‐induced changes to cerebrovascular control mechanisms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A single acute administration of MDMA has previously been shown to increase metabolic activity in most brain areas (Balogh et al,2004; Quate et al,2004; Ando et al,2006), whereas CBF was decreased (Quate et al,2004). The present study is, however, in keeping with previous chronic studies (Ferrington et al,2006) and showed a persistent effect of repeated MDMA treatment upon CMRG, with increases in a few areas against a more general background of decreased activity in the majority of ROIs, but a relative increase in CBF. Given the close relationship that normally exists between the metabolic demands of brain tissue and the CBF, the relative hyperperfusion identified in these animals must reflect lesion‐induced changes to cerebrovascular control mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…It is even possible that vascular changes not only are a symptom of mood disorders (Dunn et al,2005) but may actively contribute to the pathophysiology and functional impairment arising from serotonergic dysfunction. This is most clear experimentally where MDMA‐induced changes in cerebrovascular function have been proposed as a potential contributing factor to the oxidative stress that eventually results in 5‐HT neurotoxicity (Darvesh et al,2002; Ferrington et al,2006). However, as is the case with behavioral deficits, cerebrovascular dysfunction might become apparent only when an already vulnerable system is additionally challenged; the present study investigated the potential persistent effects of repeated MDMA exposure on neuronal and cerebrovascular function in rats subjected to an ATD challenge.…”
Section: Discussionmentioning
confidence: 99%
“…However, glucose was increased at P60 after exposure to either drug. It has been shown previously that acute MDMA results in increased cerebral glucose levels in the adult rat [18,22,23,45] as well as in the periphery [23], although decreased cerebral glucose utilization is evident over time in MDMA-treated rats [22]. On the contrary, in Dark Agouti female rats, which are poor metabolizers of MDMA, exposure results in decreased blood glucose levels [60], implying that the pharmacology and metabolism of MDMA itself may play a role in glucose utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures were carried out as described previously (Ferrington et al, 2006;Kelly et al, 1995). On the day of the experiment, animals were anesthetized with halothane (maintained at 1% in a mixture of 70% nitrous oxide and 30% oxygen), and polythene cannulae were inserted into both femoral arteries, to allow sampling of arterial blood and monitoring of arterial blood pressure, and both femoral veins, for the injection of radiolabelled tracers and barbiturate at the time of killing.…”
Section: Surgical Preparation For Fmc Studiesmentioning
confidence: 99%